The Effect of Problem-Based Learning Model on Generic Science Skills and Creative Thinking Skills in Science Learning - Haryanto, Haryanto; Asyhar, Rayandra; Astalini, Astalini; Kurniawan, Dwi Agus; Oktavia, Sri Wina; Triani, Elza; Azzahra, Miftahul Zannah; Andriyanto, Andriyanto (Jurnal Pendidikan MIPA, 2024)
This study aims to examine the impact of the Problem-Based Learning (PBL) model on students' generic science skills and creative thinking abilities in chemistry subjects at the senior high school level. Using a quasi-experimental quantitative research method, the sample consisted of 60 students from two classes, selected through stratified random sampling. The instruments used included tests for generic science skills and creative thinking and a questionnaire to assess students' responses to the PBL model. Descriptive and inferential statistical analyses revealed that students in both the Chemistry Education and Chemistry study programs demonstrated significant improvements in generic science skills and creative thinking abilities when exposed to the PBL model. The regression analysis showed a positive and significant correlation, with PBL explaining 55% of the variance in generic science skills and 52% in creative thinking abilities. These findings suggest that PBL effectively enhances critical skills in science education and encourages active learning, problem-solving, and creative thinking among students. Thus, PBL can be considered a valuable pedagogical tool in modern science education.         Keywords: active learning, chemistry education, creative thinking, generic science skills, and problem-based learning. DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1022-1036